PENGARUH PENGGUNAAN ALAT PERMAINAN EDUKATIF MAZE TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN - Novita Yulistari; Atin Fatimah; Tri Sayekti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
Cognitive abality is part of the brain thinking process in receiving and processing the information received so that children are able to remember, understand and apply all of their knowledge in solving simple problems. This research is conducted in A group of kindergarten of Islam Tirtayasa Serang - Banten. The method that used in this research is Quasi-experimental with nonequivalent control group design. Sample in this research is 28 students. The researcher takes A1 group that consist of 14 students as an experiment class and A2 group that consist of 14 students as a control class. The instrument that used in this research is observe orientation of data analysis using SPSS 22 program. The result of the research indicates that the average of cognitive skill of control class in pre-test is 22,57. Besides, the experiment class is 23,92 and The average of students’ cognitive skill in control class are increased in post-test in the amount of 2,00 % and the average of students’ cognitive skill in experiment class are increased in post-test in the amount of 6,79%. It shows that there is the effect of using maze as educative games tools toward students cognitive skill in the age 4-5 years and the influence is 2.72%. so it can be concluded that maze as the educational game can influence the cognitive abilitis of children aged 4-5 years in kindergarten Islam tirtayasa city Serang-Banten